Temperature influences water sorptivity of soil aggregates - Czachor Henryk; Lichner Ľubomír (Journal of Hydrology and Hydromechanics, 2013)
The aim of this study was to determine the potential development of water sorptivity of soil aggregates by heating. Soil aggregates were sampled from arable layer of 5 Polish soils: Haplic Luvisol 1 from Czesławice, Haplic Luvisol 2 from Wierzchucinek, Haplic Cambisol from Felin, Gleyic Mollic Cambisol from Chylice, and Haplic Phaeozem from Grabiec. Three aggregates of each soil type with minimum diameter between 4 and 10 mm were heated in the oven for at least 3 hours at temperatures 20, 100, 200, 250, and 360ºC. After each temperature treatment the soil aggregates were conditioned at the room temperature for 16 hours. Laboratory measurements of water sorptivity of soil aggregates were performed under a negative tension h0 = -2 cm using tension infiltrometer. It was found that the exposure to temperatures between 100 and 200°C tends to decrease water sorptivity of aggregates from all the studied soils but one (Haplic Luvisol 1), followed by about two- to four-fold increase in water sorptivity for exposure to temperatures of 250°C (in Haplic Luvisol 1, Haplic Luvisol 2, and Haplic Phaeozem) or 360°C (in Haplic Cambisol and Gleyic Mollic Cambisol).